FORMING A HEALTHY PSYCHOLOGICAL ENVIRONMENT IN THE FAMILY AND THE IMPACT OF GENDER STEREOTYPES ON CHILDREN'S UPbringing. (Universal International Scientific Journal, 2026)
This article analyzes the increasing information attacks in the context of globalization and their impact on the minds of young people. The role of family psychology in the formation of spiritual and moral immunity in a person is scientifically highlighted. The impact of gender stereotypes on child upbringing and the formation of social consciousness is also revealed. The results of the study show that a healthy psychological environment in the family, the principles of equality and the development of critical thinking are important factors in protecting young people from the flow of negative information.
Keywords: information attacks; spiritual immunity; family psychology